Perspektif Realisme terhadap Penggunaan Metode Inquiry Learning - Ani Budiarti; Alfauziah Rahmadani; Endang Fauziati (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
Realism is an educational philosophy that uses observations, observations, and experiments (experiments). Therefore, this flow has a step-by-step process in which learning through observation can result in experience. This study aims to (a). Describe the philosophy of education of Aristotle's realism. (b). Describe learning by using the Inquiry Learning method. The results showed that Aristotle's Realism Educational Philosophy is a philosophy that instills an understanding that is more important than memorizing and is suitable for learning using the Inquiry method. Realism Educational Philosophy Perspective on the use of the Inquiry Learning method refers to the learning objectives, namely attitudes towards the achievement of stated abilities. The attitude in question is an abstract and concrete fact.